Prognostic factors for return to work and resumption of other daily activities after traumatic hand injury - Neutel, Niels (J Hand Surg Eur Vol, 2018)
The purpose of this study was to investigate prognostic factors for the time off work, the time to resumption of activities of daily living and hobbies, and duration of complaints in patients with a traumatic hand or wrist injury. In a 10-month longitudinal prospective cohort study, 383 patients were included and interviewed in person every 2 to 3 months. Several sociodemographic, psychological and work-related prognostic factors were investigated. For the time off work, job type, diagnosis, complication, blaming someone else for the trauma and gender were all found to be individual prognostic factors in Cox regression. For the time to resumption of activities of daily living and hobbies, and duration of complaints, gender, diagnosis, treatment and complications were found to be prognostic factors in univariate analysis. Age was solely correlated with resumption of activities of daily living and the duration of complaints. Considering these prognostic factors can help predict a patient’s recovery more accurately. Level of evidence: II